Heat stress increases the use of cytosolic pyruvate for isoprene biosynthesis - Yáñez-Serrano, Ana Maria (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.